How study-related positive emotions and academic psychological capital mediate between teacher-student relationship and academic performance: a four-wave study among high school students - Carmona-Halty, Marcos; Alarcón-Castillo, Karina; Semir-González, Carla; Sepúlveda-Páez, Geraldy; Mena-Chamorro, Patricio; Barrueto-Opazo, Francisca; Salanova, Marisa (Frontiers in Psychology, 2024)
This article presents a theory-driven model in which teacher-student relationships and academic performance are indirectly related through study-related positive emotions and academic psychological capital. A sample of 1,054 Chilean high school students (50.4% females) aged 12 to 17 (M = 14.46, SD = 1.74) participated in the study. Through structural equation modelling, the direct and indirect effects of the proposed model were calculated. The results show that study-related positive emotions and academic psychological capital mediate between the teacher-student relationship and academic performance. The outcomes are significant for enhancing teaching skills through positive psychological interventions aimed at developing skills in students and thus improving students' academic performance and general well-being in educational settings.